2021
DOI: 10.1037/adb0000743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol, tobacco, and cannabis co-use on gray matter volume in heavy drinkers.

Abstract: Objective: Alcohol, tobacco, and cannabis are the three most frequently used drugs in the United States and co-use is common. Alcohol, tobacco, and cannabis use has been separately associated with altered brain structure, and alcohol and tobacco co-use results in decreases in gray matter volume. Less is known about the effect of alcohol and cannabis co-use, and alcohol, tobacco, and cannabis tri-use. Therefore, this study examined the effect of co- and tri-use on gray matter volume, a measure of brain cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…However, there have been relatively few investigations of the neurobiological correlates unique to combined use of cannabis and alcohol (for review, see Karoly et al, 2020). The Grodin et al (2021) article contributes to this emerging literature by examining differences in gray matter volume between individuals who use alcohol only versus those who co-use alcohol and cannabis in a relatively large sample of adults ( n = 237). The study also helps to tease apart differences in gray matter volume that are specific to alcohol and cannabis co-use versus triuse of alcohol, cannabis, and tobacco.…”
Section: Patterns Predictors and Short- And Long-term Outcomes Of Co-usementioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been relatively few investigations of the neurobiological correlates unique to combined use of cannabis and alcohol (for review, see Karoly et al, 2020). The Grodin et al (2021) article contributes to this emerging literature by examining differences in gray matter volume between individuals who use alcohol only versus those who co-use alcohol and cannabis in a relatively large sample of adults ( n = 237). The study also helps to tease apart differences in gray matter volume that are specific to alcohol and cannabis co-use versus triuse of alcohol, cannabis, and tobacco.…”
Section: Patterns Predictors and Short- And Long-term Outcomes Of Co-usementioning
confidence: 99%
“…Relatedly, it is also imperative that future work more comprehensively considers co-use of alcohol and cannabis within the context of the use of tobacco and other substances. For example, emerging work has highlighted the importance of assessing for the triuse of alcohol, cannabis, and tobacco (Grodin et al, 2021; Roche et al, 2019). In one diary study, 40% of SAM days involved the use of another substance, primarily tobacco use and stimulant (e.g., Adderall) use (Linden-Carmichael, Van Doren, et al, 2020).…”
Section: Patterns Predictors and Short- And Long-term Outcomes Of Co-usementioning
confidence: 99%
See 1 more Smart Citation
“…Substance use typically begins during adolescence, and patterns of behavior related to substance use are likely to be established during this time; those patterns can lead to numerous problem behaviors and health risks affecting the life course of these individuals [8,9]. Structural neuroimaging studies suggest neural consequences may be associated with substance use [10,11]. For example, smokers and cocaine users have exhibited lower gray matter volume than non-smokers and people who do not use cocaine [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Structural neuroimaging studies suggest neural consequences may be associated with substance use [10,11]. For example, smokers and cocaine users have exhibited lower gray matter volume than non-smokers and people who do not use cocaine [11][12][13]. Studies have also shown that heavy alcohol use reduces gray matter loss in different brain areas, including the frontal cortex and striatum [11,14,15].…”
Section: Introductionmentioning
confidence: 99%